Advancing Stand-Alone Photovoltaic Systems in Developing City Outskirts: Technical Solutions and Financing Approaches - Banza, Banza B.; Tungadio, Diambomba H.; Kawinda, Augustin M.; Kiseya, Flory T. (Journal of Electronics and Electrical Engineering, 2025)
This study evaluates the feasibility of electrifying isolated households using stand-alone photovoltaic systems. A technical-economic analysis was conducted in a peri-urban district of Lubumbashi (DRC), characterized by low building density and significant distance from the electricity grid. Surveys of ten households revealed that for an average load of 1,850 Wh/day, the required system includes two 350 Wp PV panels, four 250 Ah batteries, and a 1,000 W inverter. The system’s life-cycle analysis estimates an investment cost of 2,542 USD and an energy cost of 0.32 USD/kWh. Additionally, a financing model is proposed, emphasizing flexible government policies and partnerships with photovoltaic equipment producers.